Weissella paramesenteroides WpK4 plays an immunobiotic role in gut-brain axis, reducing gut permeability, anxiety-like and depressive-like behaviors in murine models of colitis and chronic stress. (November 2020) - Sandes, Sávio; Figueiredo, Naiara; Pedroso, Sílvia; Sant'Anna, Felipe; Acurcio, Leonardo; Abatemarco Junior, Mário; Barros, Patrícia; Oliveira, Fabrício; Cardoso, Valbert; Generoso, Simone; Caliari, Marcelo; Nicoli, Jacques; et al.
Graphical abstract: Mood disorders could worsen the course of inflammatory bowel disease. In this study, we evaluated the role of a probiotic bacteria in the contexts of colitis and stress, separately. W. paramesenteroides WpK4 acted as an immunobiotic, reducing inflammation at local and systemic level, promoting gut barrier and reducing anxiety-like and depressive-like behaviors in mice. Highlights: In mice with colitis, WpK4 promoted the epithelial barrier, reducing gut leakage. WpK4 triggered Il22 expression, which could have contributed to mucosal healing. In stressed mice, WpK4 reduced anxiety-like and depressive-like behaviors. These beneficial effects could be related to an immunomodulation in gut and brain. Abstract: The relationship between inflammatory bowel disease (IBD) and mood disorders is complex and involves overlapping metabolic pathways, which may determine comorbidity. Several studies have been shown that this comorbidity could worsen IBD clinical course. The treatment of ulcerative colitis is complex, and involves traditional therapy to promote the function of epithelial barrier, reducing exacerbated inflammatory responses. Recently, it has been shown that some probiotic strains could modulate gut-brain axis, reducing depressive and anxiety scores in humans, including IBD patients. Accordingly, this study aimed to evaluate the role of Weissella paramesenteroides WpK4 in murine models of ulcerative colitis and chronic stress. It was observed that bacterium ingestion improved health of colitis mice, reducing intestinal permeability, besides improving colon histopathological appearance. In stressed mice, bacterial consumption was associated with a reduced anxiety-like and depressive-like behaviors. In both assays, the beneficial role of W. paramesenteroides WpK4 was related to its immunomodulatory feature. It is possible to state that W. paramesenteroides WpK4 exerted their beneficial roles in gut-brain axis through their immunomodulatory effects with consequences in several metabolic pathways related to intestinal permeability and hippocampal physiology.